2021
DOI: 10.1126/sciadv.abh0363
|View full text |Cite
|
Sign up to set email alerts
|

Intravital imaging technology guides FAK-mediated priming in pancreatic cancer precision medicine according to Merlin status

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly metastatic, chemoresistant malignancy and is characterized by a dense, desmoplastic stroma that modulates PDAC progression. Here, we visualized transient manipulation of focal adhesion kinase (FAK), which integrates bidirectional cell-environment signaling, using intravital fluorescence lifetime imaging microscopy of the FAK-based Förster resonance energy transfer biosensor in mouse and patient-derived PDAC models. Parallel real-time quantification of the FUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 86 publications
0
31
0
Order By: Relevance
“…Indeed, previous work has shown that collagen cross-linking by lysyl oxidases and changes in tumour stiffness is critically important in driving the progression of breast cancer and that blocking this crosslinking can block tumour progression 9 . Further work has also shown that the biophysical properties of the ECM can also modify treatment response in triple-negative breast cancer 39 , and agents that modulate stiffness-dependent NF-kB or JNK activity could enhance therapeutic efficacy in TNBC patients 40 as well as in other cancer types 41 . Therefore, uncovering elements which regulate matrix assembly and organisation, and the role that they play in solid tumour progression will be critical to dissecting the role of the matrix in cancer 1 .…”
mentioning
confidence: 99%
“…Indeed, previous work has shown that collagen cross-linking by lysyl oxidases and changes in tumour stiffness is critically important in driving the progression of breast cancer and that blocking this crosslinking can block tumour progression 9 . Further work has also shown that the biophysical properties of the ECM can also modify treatment response in triple-negative breast cancer 39 , and agents that modulate stiffness-dependent NF-kB or JNK activity could enhance therapeutic efficacy in TNBC patients 40 as well as in other cancer types 41 . Therefore, uncovering elements which regulate matrix assembly and organisation, and the role that they play in solid tumour progression will be critical to dissecting the role of the matrix in cancer 1 .…”
mentioning
confidence: 99%
“…Another important finding was the improvement of LN metastasis diagnosis with the application of EV-packaged hnRNPA1. Currently, the assessment of LN status of PDAC mainly relies on imaging-based approaches, which are inaccurate, especially for early lesions ( 50 ). Therefore, monitoring LN metastasis in PDAC remains greatly challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, G q/11 activating mutations have been found to modulate YAP/TAZ activity via focal adhesion kinase (FAK), highlighting potential in inhibition of FAK as a cancer therapy, with in vitro validation in UM cell lines [ 245 ]. This therapeutic approach is validated experimentally, as NF2 expression levels predict efficacy of FAK inhibition in cells derived from pancreatic cancer patients [ 246 ]. Additionally, an improved response is observed with NF2 KD in vitro and in vivo [ 246 ], suggesting that YAP/TAZ activity likely positively correlates with sensitivity to FAK inhibition, given NF2’s function as an activator of the Hippo kinase cascade ( Figure 1 ).…”
Section: Therapeutics and Hippo Signallingmentioning
confidence: 99%
“…This therapeutic approach is validated experimentally, as NF2 expression levels predict efficacy of FAK inhibition in cells derived from pancreatic cancer patients [ 246 ]. Additionally, an improved response is observed with NF2 KD in vitro and in vivo [ 246 ], suggesting that YAP/TAZ activity likely positively correlates with sensitivity to FAK inhibition, given NF2’s function as an activator of the Hippo kinase cascade ( Figure 1 ).…”
Section: Therapeutics and Hippo Signallingmentioning
confidence: 99%